ATHLETES ENGAGEMENT MODEL: A GENDER - Paulo Martins; António Rosado; Vítor Ferreira; Jolita Vveinhart (Federación Extremeña de Balonmano; University of Extremadura, 2015)
Investigation from a diversity of theoretical perspectives displays that one of the best predictors of children's continuing involvement in sports is the development of positive feelings for sport involvement (e.g. Martins, Rosado, Ferreira & Biscaia, 2014). In sport, the concept of engagement reflects the energy in action, the connection between the person and the activity, and it is considered as a form of active involvement between the individual and the task (Russell, Ainley, & Frydenberg, 2005). In sport, the concept of athletes' engagement reflects a relatively stable and long lasting experience that is generically characterized through positive emotions and cognitions when engaged in the act of practicing the given activity (Lonsdale, Hodge, & Raedeke, 2007). Therefore, the analysis of experiences related to engagement is important in order to understand sport participation, and how its different levels can condition the social involvement. In addition, these studies failed to examine potentially important gender differences in engagement among athletes. Therefore, the study of athletes by evaluating their engagement levels comparing genders, can contribute towards shedding light on decisive aspects pertaining to its social involvement within ethical dimensions as well as personal and social responsibility, on which research is still lacking. Objectives: The purpose of this study was to investigate the impact of gender on engagement in a sport scenario among youth athletes.